The influence of romanticism on the evolution of the transcendental etudes of Franz Liszt - Low, Michael Meow Yin (College of Music, 2014)
This thesis sets out to investigate the musical and Romantic ideas that may have influenced Liszt during the composition of the three versions of the 'Transcendental' Etudes in relation to the pianistic and musical evolution of the work. The musical and pianistic content of the juvenile etude pour le piano en douze exercices (1827) takes after the didactic exercises of Karl Czerny. The intermediate version, known as the Grandes Ãtudes (1839), was conceived at the height of Liszt's performing career and develops the principal thematic ideas of its predecessor whilst incorporating the virtuoso piano technique developed by Liszt's contemporaries, Thalberg and Chopin, as well as the advanced chromaticism characteristics of the latter's music. Crucial to the realisation of the intermediate version with its almost superhuman technical demands is also the influence of Paganini. The final version entitled etudes d'execution trancendente (1852) features a facilitation of some of the technically most demanding passages, as well as the addition of programmatic titles to ten of the twelve etudes. The relationship between programmatic intention and changes to the musical content is not as direct a one as may be supposed, since the vast majority of the radical changes to the musical content did not occur with the (explicit) addition of programmatic/descriptive intention in 1852, but rather in the 1839 version. This poses the question of whether the intermediate version was already implicitly programmatic/descriptive in intention, or whether the titles of the 1852 version were mere 'afterthoughts', added to works that had been transformed for other reasons. The balance of evidence gathered by the author supports the former view.